Adoption of improved crop varieties by involving farmers in the e-wallet program in Nigeria - Joseph I. Uduji; Elda N. Okolo-Obasi (African Governance and Development Institute (AGDI), 2018)
The amount of improved seed used in Nigeria is extremely low. Overall, only 5 to 10 percent of cultivated land is planted with improved seeds, and about 10 percent of rural farmers use improved varieties. The objective of this investigation was to identify determinants of adoption of improved seed by farmers not participating in and those participating in the federal government 's e-wallet program in Nigeria. We determined the impact of the e-wallet program on adoption of improved seed in rural areas. One thousand, two hundred (1200) rural farmers were sampled across six geopolitical zones of Nigeria. Results from the use of a bivariate probit model indicated that the e-wallet program continued to become increasingly popular among rural farmers; and that farmers ' literacy, ownership of a mobile phone, value output, mobile network coverage, power for charging phone batteries and contact with extension agents were the positive determinants of farmer participation in thee-wallet program. Cultural obstacles to married women, growers ' age , and increased distance to registration and input collection centers reduced farmers' tendency to participate in the e- wallet program. The results also show ed that rural farmers depend ed on the e-wallet program for increased use and adoption of improved seed in Nigeria, to boost food security in sub- Saharan Africa. The results suggest ed the need for an improved e-wallet model by lessening constraints mostly associated with rural information and communication infrastructure, and distance to the registration and input collection centers.
Keywords: J43; O40; O55; Q10; 330; Agricultural transformation agenda; bivariate probit model; federal government of Nigeria; growth enhancement support scheme; mobile phone-based technologies; sub-Saharan Africa